A systematic review of biocompatibility and safety of orthodontic clear aligners and transparent vacuum-formed thermoplastic retainers: Bisphenol-A release, adverse effects, cytotoxicity, and estrogenic effects - Marzie Yazdi; Hanie Daryanavard; Alireza Hashemi Ashtiani; Mehrnaz Moradinejad; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2023)
Background: An ever-increasing demand is seen for clear aligners and transparent vacuum-formed retainers. They are esthetic and convenient. However, the biomaterials used in these appliances might pose biological safety and biocompatibility threats in terms of their bisphenol-A (BPA) release, cytotoxicity, adverse effects, and estrogenic effects. Due to the controversial results and the lack of any systematic reviews in this regard, we conducted this systematic review. Materials and Methods: Web of Science, PubMed, Cochrane, Scopus, and Google Scholar as well as references of the found articles were searched (independently by 3 researchers) up to December 22, 2021, to find studies relevant to the biocompatibility of clear aligners and thermoplastic retainers. The search keywords were a combination of the following (and more): Essix, vacuum-formed aligner, thermoplastic aligner, clear aligner, Invisalign, vacuum-formed retainer, BPA release, monomer release, cytotoxicity, estrogenicity, biocompatibility, chemical properties, and oral epithelial cell. As eligibility criteria, articles in all languages would be included as long as their text could be translated clearly using online translators or by professional translators; all types of publications (article, book, and thesis) would be included if containing relevant studies and information; they should have been on clear liners or thermoplastic retainers; and they should have been on biocompatibility, safety, cytotoxicity, or estrogenicity of clear aligners or thermoplastic retainers. There were no restrictions on the type of study (randomized clinical trials, experimental in vitro studies). Studies focusing merely on the mechanical properties of clear aligners or thermoplastic retainers (without examining their chemical properties) would be excluded. The risk of bias was assessed. Results: The risk of bias was rather low. However, the methodologies of the studies were quite different. Overall, 16 articles (1 randomized clinical trial and 15 in vitro studies) were identified. The data for BPA release were reported in four articles (1 clinical trial and 3 in vitro studies). Quantitatively speaking, the amount of released BPA reported by in vitro studies was very low, if not zero. However, the BPA level was very high in the only randomized clinical trial. Many adverse effects were linked to using clear aligners or transparent retainers, including pain and soft-tissue issues such as burning, tingling, sore tongue, lip swelling, blisters, ulceration, dry mouth, periodontal problems, and even systemic problems such as difficulty in breathing. Besides these biological adverse effects, oral dysfunctions and speech difficulties and tooth damage may be associated with clear aligners and should as well be taken into consideration. Conclusion: Given the very high levels of BPA leach observed in the only clinical trial and considering other possible dangers of small traces of BPA (even at low doses) and also given the numerous adverse events linked to clear aligners or transparent retainers, it seems that safety of these appliances might be questionable and more clinical studies of biocompatibility are needed in this regard.